Warisan Tambang Batu Bara Ombilin-Sawahlunto: Empat Tahun Setelah Penetapan Warisan Dunia dan Ingatan Kolektif Lainnya - Sudarmoko, Sudarmoko; Putra, Heru Joni (Universitas Andalas, 2024)
The Ombilin coal mine in Sawahlunto, West Sumatra, is one of the sites designated as a UNESCO World Heritage Site in 2019. The designated objects and attributes include not only the coal mining area but also the railway network spanning seven districts and cities, as well as the warehouse at Silo Gunung in Padang City. This article provides an update on the current condition of several designated objects and attributes, particularly regarding managing this World Heritage Site, which was newly designated during the COVID-19 pandemic. Several objects and attributes have received little attention regarding activation and maintenance efforts, compounded by the absence of a management body or integrated management system with the authority to design and implement strategic management programs for WTBOS. Additionally, this article analyzes the impact of high technology introduced by the development of the Ombilin coal mine and its connection to the culture of West Sumatra. Collective memory, as recorded in literary works, travelogues, and biographies, is also explored to illustrate how the community perceives and experiences the presence of WTBOS and its railway network. These collective memories are essential to uncover as a complement to the information and data already presented in the WTBOS nomination dossier for World Heritage status.